2020
DOI: 10.3847/1538-3881/ab7023
|View full text |Cite
|
Sign up to set email alerts
|

Arecibo Radar Astrometry of the Galilean Satellites from 1999 to 2016

Abstract: Harmon et al. Arecibo radar observations from 1992 provided some of the most precise line-of-sight distance (ranging) measurements of Ganymede and Callisto to date. We report 18 new ranges obtained at Arecibo from 1999 to 2016, among which are the first measurements of Io and Europa. We also report accompanying line-ofsight velocity (Doppler frequency) measurements. In 2015, we detected Europa, Ganymede, and Callisto with time-delay (range) resolutions as fine as 10 μs (1.5 km) while Io was detected with 70 μs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 36 publications
0
3
0
Order By: Relevance
“…The most precise measurements from Earth are obtained by mutual occultations of the satellites (which occur every 6 years), occultations of stars by the satellites (which are valuable but rare), and radar ranging. Radar ranging from Arecibo has obtained the most precise positional measurements on Io from Earth to date, with a precision of just over 5 km (Brozović et al 2020). Past research has found contradictory results for the magnitude and direction of Io's secular orbital evolution (e.g., Goldstein & Jacobs 1995, Aksnes & Franklin 2001.…”
Section: Orbital Evolution Of Iomentioning
confidence: 99%
“…The most precise measurements from Earth are obtained by mutual occultations of the satellites (which occur every 6 years), occultations of stars by the satellites (which are valuable but rare), and radar ranging. Radar ranging from Arecibo has obtained the most precise positional measurements on Io from Earth to date, with a precision of just over 5 km (Brozović et al 2020). Past research has found contradictory results for the magnitude and direction of Io's secular orbital evolution (e.g., Goldstein & Jacobs 1995, Aksnes & Franklin 2001.…”
Section: Orbital Evolution Of Iomentioning
confidence: 99%
“…The case of Galilean moons is a critical example because Jupiter's brightness in the Field of View (FoV) would quickly saturate the CCD, thus providing positions with uncertainties that range between 100 and 150 milliarcseconds (mas; Kiseleva et al 2008). This scenario motivates the search for alternative methods for the astrometry of these satellites, such as the mutual phenomena events (Aksnes & Franklin 1976;Aksnes et al 1984;Emelyanov 2009;Arlot et al 2014;Saquet et al 2018;Morgado et al 2019c, and references therein), mutual approximations (Morgado et al 2016(Morgado et al , 2019a, radar astrometry (Brozović et al 2020), and stellar occultations (Morgado et al 2019b), among others.…”
Section: Introductionmentioning
confidence: 99%
“…The case of Galilean moons is a critical example since Jupiter's brightness in the Field of View (FoV) would quickly saturate the CCD, thus providing positions with uncertainties that range between 100 and 150 milliarcseconds (mas) (Kiseleva et al 2008). This scenario motivates the search for alternative methods for the astrometry of these satellites, for example, the mutual phenomena events (Aksnes & Franklin 1976;Aksnes et al 1984;Emelyanov 2009;Arlot et al 2014;Saquet et al 2018;Morgado et al 2019c, and references therein), mutual approximations (Morgado et al 2016(Morgado et al , 2019a, radar astrometry (Brozović et al 2020), stellar occultations (Morgado et al 2019b), among others.…”
Section: Introductionmentioning
confidence: 99%